2004
DOI: 10.1016/j.femsim.2004.03.003
|View full text |Cite
|
Sign up to set email alerts
|

TheHelicobacter pyloriplasticity region locusjhp0947–jhp0949is associated with duodenal ulcer disease and interleukin-12 production in monocyte cells

Abstract: Colonization with Helicobacter pylori always results in chronic gastritis, which is controlled by infiltration of mononuclear cells and the subsequent release of cytokines like interleukin (IL)-12. To identify H. pylori factors involved in inducing cytokine production in mononuclear cells, a random H. pylori mutant library was screened for the inability to induce IL-12 production in monocyte THP-1 cells. Of the 231 random mutants screened, one mutant (M1) showed a consistent twofold decrease in the amount of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
41
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 25 publications
7
41
1
Order By: Relevance
“…Interestingly, JHP0950 has been suggested as a marker for H. pylori strains from patients with gastric extranodal marginal-zone-B-cell lymphoma of the MALT type (29). Other genes in PZ2 and previously reported as associated with DU, i.e., JHP0947 and JHP0949 (12), are in the vicinity of two genes, JHP0950 and JHP0951, found by us to be associated with DU. In fact, it was recently suggested that JHP0950 may form part of an operon that includes the JHP0949 gene (37,55).…”
Section: Vol 77 2009 Novel Cancer-associated H Pylori Genes 2207supporting
confidence: 64%
See 1 more Smart Citation
“…Interestingly, JHP0950 has been suggested as a marker for H. pylori strains from patients with gastric extranodal marginal-zone-B-cell lymphoma of the MALT type (29). Other genes in PZ2 and previously reported as associated with DU, i.e., JHP0947 and JHP0949 (12), are in the vicinity of two genes, JHP0950 and JHP0951, found by us to be associated with DU. In fact, it was recently suggested that JHP0950 may form part of an operon that includes the JHP0949 gene (37,55).…”
Section: Vol 77 2009 Novel Cancer-associated H Pylori Genes 2207supporting
confidence: 64%
“…Other studies have reported that genes located in the PZs, such as jhp0947 and jhp0949, are associated with disease (12,37,47). The dupA gene was associated with an increased risk for duodenal ulcer (DU) and a low risk for gastric atrophy and cancer (31).…”
mentioning
confidence: 99%
“…The latter usually have an aberrant GϩC content and often carry genes involved in virulence. A striking example of this in H. pylori is the cag PAI, but other plasticity regions have also been suggested to play a role in the pathogenesis of H. pylori infection (115,357,462,545).…”
Section: Microbiology Of H Pylorimentioning
confidence: 99%
“…IL-12-deficient mice have also reduced gastric inflammatory infiltration and are unable to clear H pylori infection [46] . Several virulence factors are reported to promote Th1 responses, including the plasticity region locus jhp0947-jhp0949 which is associated with duodenal ulcer disease [47] and the H pylori-NAP [29] . The Th1/Th2 balance is also influenced by phase-variable expression of Lewis bloodgroup antigens and genomic DNA recombination [48,49] .…”
Section: H Pylori-driven Th1-immune Responsementioning
confidence: 99%